Evaluation of some proposed models for shear design of reinforced concrete beams - Wilson, Hendrik J.(Hendrik Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1987.